2005
DOI: 10.1016/j.jcta.2004.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The minimum period of the Ehrhart quasi-polynomial of a rational polytope

Abstract: If P ⊂ R d is a rational polytope, then i P (n) := #(nP ∩ Z d ) is a quasi-polynomial in n, called the Ehrhart quasi-polynomial of P . The minimum period of i P (n) must divide D(P ) = min{n ∈ Z >0 : nP is an integral polytope}. Few examples are known where the minimum period is not exactly D(P ). We show that for any D, there is a 2-dimensional triangle P such that D(P ) = D but such that the minimum period of i P (n) is 1, that is, i P (n) is a polynomial in n. We also characterize all polygons P such that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…When P is a simplex, we deduce a formula for the generating series of f Pg (m) (Proposition 6.1). A pseudo-integral polytope is a rational polytope whose Ehrhart quasi-polynomial is a polynomial (see the work of De Loera, McAllister and Woods [10,24]), and we apply this formula to construct new pseudo-integral polytopes in all dimensions in Section 10.…”
Section: Introductionmentioning
confidence: 99%
“…When P is a simplex, we deduce a formula for the generating series of f Pg (m) (Proposition 6.1). A pseudo-integral polytope is a rational polytope whose Ehrhart quasi-polynomial is a polynomial (see the work of De Loera, McAllister and Woods [10,24]), and we apply this formula to construct new pseudo-integral polytopes in all dimensions in Section 10.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is called period collapse and has been subject to active research in the last years. McAllister and Woods [11] studied the 1-and 2-dimensional case with the result that period collapse does not occur in dimension 1, and they gave a characterization of those rational polygons in dimension 2 whose Ehrhart quasi-polynomial is a polynomial. They also showed that the minimal periods of G i (P , ·) are not necessarily decreasing with i.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-period collapse cannot happen in dimension 1, but there exist families of polygons in R 2 with arbitrarily large denominators whose minimum quasi-periods are 1. This result was originally proved in [MW05], where the proof of polynomiality involved subdividing the polygons into polygonal pieces whose Ehrhart quasi-polynomials could be computed. The periodic parts for these pieces could be seen by inspection to cancel, with the result that the counting function for the entire polygon was a polynomial.…”
Section: Introductionmentioning
confidence: 99%